FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAMPUAN AUDITOR MENDETEKSI KECURANGAN (FRAUD) (Studi Empiris Pada BPK Perwakilan Provinsi Jawa Tengah) - Ratih Sariningrum, 14.05.52.0285; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2019)
The purpose of this research is to analyse the influence of audit experience, competency, independency, professional skepticism, workload and time pressure towards auditor’s ability to detecting fraud on the auditor BPK Representative of Province in Central of Java. The population of this research are all auditor which have followed Education and Training of Functional Posision of Auditor (JFP) and 2 years minimal job experience as auditor. Sampling was conducted using a purposive sampling method and number of samples of 101 respondents. Primary data collection method used is multiple regression model. The results showed that experience, competence, professional skepticism had a significant positive effect on the ability to detect fraud. While independence and time budget pressure have a positive and insignificant effect. Workload has a significant negative effect on the ability to detect fraud.